What Do We Know About Teamwork in Chinese Hospitals? A Systematic Review - Wang, Hujie; Buljac-Samardzic, Martina; Wang, Wenxing; van Wijngaarden, Jeroen; Yuan, Shasha; van de Klundert, Joris (Frontiers in Public Health, 2021)
Background: Improving quality of care is one of the primary goals in current Chinese hospital reforms. Teamwork can play an essential role. Characteristics of teamwork and interventions for improving teamwork in hospitals have been widely studied. However, most studies are from Western contexts; evidence from China is scarce. Because of the contextual differences between China and Western countries, empirical evidence on teamwork from Western hospitals may have limited validity in China. This systematic review aims to advance the evidence base and understanding of teamwork in Chinese hospitals. Methods: Both English and Chinese databases were searched for articles until February 6, 2020. We included the studies that empirically researched teamwork in Chinese hospitals. Both deductive and inductive approaches were used to analyze data. The Mixed Methods Appraisal Tool was used to assess their methodological quality. Results: Seventy articles were included. The results are presented in two categories: Teamwork components and Team interventions. The evidence regarding the relationships among inputs, processes, and outcomes is scarce and mostly inconclusive. The only conclusive evidence shows that females perceive better team processes than males. Similar types of training and tools were introduced as can be found in Western literature, all showing positive effects. In line with the Chinese health reform, most intervention studies regard the introduction of multidisciplinary teams (MDTs). The evidence on the MDT implementation reveals that they have led to lower complication rates, shorter hospital stays, higher diagnosis accuracy, efficiency improvement, and a variety of disease-specific clinical outcomes. Evidence on the effect on patient survival is inconclusive. Conclusion: The Chinese studies on teamwork components mainly focus on the input-process relationship. The evidence on this relationship is, however, mostly inconclusive. The intervention studies in Chinese hospitals predominantly focus on patient outcomes rather than organizational and employee outcomes. The introduction of training, tools, and MDTs generally shows promising results. The evidence from primary hospitals and rural areas, which are prioritized in the health reforms, is especially scarce. Advancing the evidence base on teamwork, especially in primary hospitals and rural areas, is needed and can inform policy and management to promote the health reform implementation.